Pelatihan Pemetaan Risiko dan Laporan Kasus Berbasis Epidemiologi oleh Kader Desa Siaga - Sudirman, Sudirman; Ramli, Rachmat; Harlina, Harlina; Yermi, Yermi; Sahabuddin, Sahabuddin (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Village Alert Cadres are at the forefront of early detection and response to health problems at the village level. Cadres' limited understanding of epidemiology concepts and risk reporting has weakened the early warning system. The objective of this activity was to increase the capacity of cadres in health risk mapping and case reporting based on basic epidemiological principles. The activity was implemented through training, risk mapping simulations, and practice in preparing case reports. Evaluation results showed a significant increase in cadres' understanding and skills after the training. It is hoped that this activity will serve as a replicable training model in other areas to strengthen community-based health systems.